Technological sovereignty and strategic dependencies: The case of the photovoltaic supply chain - Serenella Caravella; Francesco Crespi; Giacomo Cucignatto; Dario Guarascio (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
This work sheds new light on the Photovoltaic Supply Chain (PVSC), providing fresh evidence on structural dependencies (SDs) and (asymmetrically distributed) technological capabilities. Bridging the perspectives of 'technological sovereignty' and 'strategic autonomy', a number of contributions are provided. First, we carry out a fine-grained mapping of the PVSC, combining trade and patent data. Second, we assess the long-term evolution of trade and technological hierarchies, documenting processes of polarization and growing SDs. Third, we zoom-in on critical PV areas (i.e. products and related technologies), providing a 'strategic intelligence' activity which may prove useful for tailoring trade, industrial and innovation policies. Fourth, we explore the relationship between technological specialization and productive capabilities showing that, in the upstream segment, reinforcing the former may help mitigating SDs.
Keywords: C23; F18; O31; O38; Q42; 330; Technological sovereignty; Strategic dependency; Photovoltaic industry; Trade; Patents